Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/life10110291
|View full text |Cite
|
Sign up to set email alerts
|

Six ‘Must-Have’ Minerals for Life’s Emergence: Olivine, Pyrrhotite, Bridgmanite, Serpentine, Fougerite and Mackinawite

Abstract: Life cannot emerge on a planet or moon without the appropriate electrochemical disequilibria and the minerals that mediate energy-dissipative processes. Here, it is argued that four minerals, olivine ([Mg>Fe]2SiO4), bridgmanite ([Mg,Fe]SiO3), serpentine ([Mg,Fe,]2-3Si2O5[OH)]4), and pyrrhotite (Fe(1−x)S), are an essential requirement in planetary bodies to produce such disequilibria and, thereby, life. Yet only two minerals, fougerite ([Fe2+6xFe3+6(x−1)O12H2(7−3x)]2+·[(CO2−)·3H2O]2−) and mackinawite (Fe[Ni]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 250 publications
(344 reference statements)
2
16
0
Order By: Relevance
“…Among them are minerals such as mackinawite (FeS) and its Ni-containing form, greigite (Fe 3 S 4 ) and violarite (FeNi 2 S 4 ). Some of these are considered key minerals [ 130 ] for the AHV and geoelectrochemistry models for the emergence of life. The CO 2 reduction electrocatalysis of the minerals is the most common reaction that was investigated.…”
Section: Experimental Setups and Results Investigating The Ahv Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them are minerals such as mackinawite (FeS) and its Ni-containing form, greigite (Fe 3 S 4 ) and violarite (FeNi 2 S 4 ). Some of these are considered key minerals [ 130 ] for the AHV and geoelectrochemistry models for the emergence of life. The CO 2 reduction electrocatalysis of the minerals is the most common reaction that was investigated.…”
Section: Experimental Setups and Results Investigating The Ahv Modelmentioning
confidence: 99%
“…The properties and environmental utility of this mineral are already known, even though they are not related to CO 2 reduction [ 133 , 134 ]. Besides its importance—once already mentioned for the AHV model, which considers it a key mineral for the emergence of life [ 130 ]—there has been little exploration of its electrochemistry in experiments applying in the AHV model. Evidence has shown that mackinawite interacts with CO and CO 2 under pH 6.8 conditions at room temperature [ 135 ].…”
Section: Experimental Setups and Results Investigating The Ahv Modelmentioning
confidence: 99%
“…UV has also been heralded as an energy source to free-up an electron from tricyanocuprate Cu(CN) 3 though again, exactly how the latter is produced in sufficient quantities, or at all, is also not demonstrated [ 60 ]. The Earth’s volatisphere was simply too oxidized to support a substantial source of that poison [ 61 , 62 , 63 ].…”
Section: Dirty Chemistrymentioning
confidence: 99%
“…The reasoning goes that as the olivine-rich mantle is subjected to pressures beyond ~21 GPa in the lower mantle, it tends to metamorphose to perovskite, a mineral that requires a 3 + valence metal, normally aluminum. However, as the concentrations of Al 3+ in the mantle are too low to meet this entire need, iron in the olivine disproportionates, with Fe 3+ deputizing for the lacking Al 3+ , while the native iron Fe 0 tends to gravitate to the core [ 61 , 62 , 63 , 85 ]. The result is a relatively oxidized volatisphere comprising CO 2 > H 2 O >> N 2 [ 85 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 ].…”
Section: The “Pond” In the Hellish Hadeanmentioning
confidence: 99%
“…Hazen et al [ 2 ] pointed out that clay minerals have evolved over time, and there is little doubt that the Great Oxidation Event changed the composition of clays and other minerals exposed to molecular oxygen. Russell and Ponce [ 3 ] proposed a set of ‘must have’ minerals related to life’s origin in hydrothermal vent conditions, but it is uncertain whether these were available on the prebiotic Earth. On the other hand, parameters such as temperature, evaporation, pH, dissolved salts and concentration of organic solutes are variables in today’s hot springs and are likely to be analogous to the same variables four billion years ago.…”
Section: Prebiotic Analogue Sitesmentioning
confidence: 99%